(3GdeONd ddYdhe GdbGfhfjI (B:s (3GdfXQjI GdYGeI ddbGfhf (B/s - (3GdNdjdj,MHjH EHQGgje s ((3GdLRGFQ (B:s (3OjhGf GdeWHhYGJ GdLGeYjI ,s, 1992)
(3GdeHMK GdGhd JYQja GdbGfhf GeG GdaUd GdKGfj GdebGQfI Hjf bhGYO GdbGfhf h ZjQgG ef bhGYO GdSdhc GdELJeGYj GdaUd GdKGdK GKQ cd ef GdPgHjf GdaQOj h GdGTJQGcj aj JMOjO fWGb GdbGfhf HhLg YGe GdaUd GdQGHY GdUdI Hjf GdbGfhf h GdYdhe GdGLJeGYjI GdGNQi GdaUd GdNGeS GdYdhe GdbGfhfjI GdeNJdaI h GdUdI HjfgG(B.s
Keywords: (3GdYdhe GdbGfhfjIs; (3GdbGfhf s